2021
DOI: 10.5114/wiitm.2021.103918
|View full text |Cite
|
Sign up to set email alerts
|

Age and risk of major complications in patients undergoing radical cystectomy for muscle invasive bladder cancer.

Abstract: Introduction Radical cystectomy is the treatment of choice for patients with muscle invasive bladder cancer (MIBC), but it may be unsafe in older patients. Aim In this study, we investigated whether age and selected clinical characteristics were associated with outcomes of radical cystectomy. Material and methods We enrolled 434 patients with MIBC who underwent radical cystectomy between 2012 and 2016, and we classified them into three age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…With precise preoperative preparation, meticulous intraoperative hemostasis, a minimally invasive method of surgery (laparoscopic or robot-assisted), and the correct post-operative management, it is possible to significantly reduce surgery complication rates. In our previous study, older age alone did not increase the risk of major postoperative complications, prolonged hospital stays, or blood loss among patients who were subjected to radical cystectomy [30]. This concurs with other studies [31][32][33].…”
Section: Discussionsupporting
confidence: 90%
“…With precise preoperative preparation, meticulous intraoperative hemostasis, a minimally invasive method of surgery (laparoscopic or robot-assisted), and the correct post-operative management, it is possible to significantly reduce surgery complication rates. In our previous study, older age alone did not increase the risk of major postoperative complications, prolonged hospital stays, or blood loss among patients who were subjected to radical cystectomy [30]. This concurs with other studies [31][32][33].…”
Section: Discussionsupporting
confidence: 90%
“…This would increase the hospitalization duration, which is higher in IC patients. Adamczyk et al [13] reported that IC becomes a significant predictor of prolonged hospital stay (> 7 days) compared to TUU, with an odds ratio of 6.13 (95% CI: 3.40-11.39, p < 0.001). Our meta-analysis found that the IC group had a significantly higher mean duration of hospitalization than the TUU group, with a mean difference of 3.80 (95% CI: 2.27-5.32; p < 0.001; I 2 = 92%).…”
Section: Discussionmentioning
confidence: 99%
“…DeNunzio et al [12] and Fuschi et al [14] reported a higher complication rate (CDCS grade ≥ 3) in the IC group. In contrast, six other studies reported no difference in the proportion of major complications (CDCS grade ≥ 3) between the two groups [9,13,[18][19][20][21]. Moreover, Kadoriku et al [18] reported no significant difference in the proportion of major complications in 2 different periods, 30 days and 90 days postoperatively.…”
Section: Late Complicationsmentioning
confidence: 94%
See 1 more Smart Citation